Compact wideband metamaterial quadrature coupler for 5G beamforming applications - Keriee, Hussam Hamid; Abd. Rahim, Mohamad Kamal; Nayyef, Nawres Abbas; Ayop, Osman; Al Gburi, Ahmed Jamal Abdullah (Wydawnictwo SIGMA-NOT, 2023)
A design of a compact wideband quadrature coupler based on metamaterial is presented at 3.5 GHz. The quadrature coupler is a significant component in beamforming networks with problems of narrow bandwidth and bulky size. The proposed quadrature coupler is designed with the implementation of composite right/left-handed (CRLH) arms metamaterial transmission line (TL). The metamaterial fingers are implemented in each branch section to reduce the size and improve the bandwidth. The proposed coupler is simulated using CST software and then fabricated on the FR4 substrate with (εr=4.4 and h=1.6 mm). The coupler performance achieved a fractional bandwidth of 55.42% operated at 2.25 GHz to 4.19 GHz. The coupling factor at 3.5 GHz is -3 ±0.5 dB with a phase difference of 88.01°. Compared to conventional BLC, the proposed coupler achieved a size reduction of 40.43%. The proposed coupler is suitable to be used in future 5G beamforming applications.